Statistical analysis of the measured strength parameters of the fresh main intracranial arteries - Truchel, Krzysztof; Wojtas, Krzysztof; Rzepliński, Radosław; Sługocki, Mikołaj; Łopianiak, Iwona; Butruk-Raszeja, Beata; Jędrzejczak, Krystian; Orciuch, Wojciech; Gierycz, Paweł; Krajewski, Paweł; Ciszek, Bogdan; Makowski, Łukasz (Frontiers in Bioengineering and Biotechnology, 2025)
This study presents the strength parameters of the major intracranial arteries: basilar artery (BA), anterior cerebral arteries (ACA), both left (LACA) and right (RACA), and middle cerebral arteries (MCA), both left (LMCA) and right (RMCA) and the anterior communicating artery (ACoA) obtained by performing single rupture tensile tests on fresh human biological specimens. The measured parameters included maximum Young’s modulus, E, ultimate strength, Rm, rupture strength, Ru, and rupture strain, A, allowing the determination of mean values for each artery type. They were also the basis for a multiple comparison analysis showing that ACA and ACoA significantly differ from BA and MCA. The study also showed that the measured strength parameters are directly dependent on the thickness of the arterial wall, and this effect is about 4–5 times greater for the ACA group and 1.5–3 times greater for ACoA than in the BA + MCA group. Finally, a limit value of maximum relative longitudinal strain of 7% was proposed at low risk of rupture during neurovascular procedures. Obtained parameters and findings have potential applications in optimizing neurointerventional devices, tissue engineering of arterial phantoms or tissue scaffolds, and computational simulations in cerebral hemodynamics.